The Influence of Work–Life Balance and Person–Organization Fit onIntention to Leave: The Mediating Role of Job Satisfaction among Boarding School Mentors in Padang, Indonesia - Rani Iqasari; Sulastri Sulastri (Yayasan Edukasi Cakrawala Nusantara, 2026)
This study aims to analyze the effect of Work-Life Balance (WLB) and Person-Organization Fit (PO-Fit) on Intention to Leave (ITL) with Job Satisfaction (JS) as a mediator among dormitory counselors at boarding schools in Padang City. A quantitative approach was used with a population of all active counselors at Ar Risalah and Sabbihisma (n=77) and purposive sampling. Data analysis was conducted using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results showed that WLB and PO-Fit negatively affected ITL, meaning that the better the work-life balance and fit of the individual with the organization, the lower the counselor's intention to leave. Job Satisfaction also negatively affected ITL and acted as a significant mediator in the relationship between PO-Fit and ITL, but was not significant in the relationship between WLB and ITL. These findings emphasize the importance of the fit between individual values, culture, and goals with the organization in increasing Job Satisfaction and reducing turnover intention. This research provides strategic implications for boarding school management in increasing job satisfaction, retaining mentors, and ensuring the continuity of the student character development process.